High-Risk Preterm Infant Born to a Mother With COVID-19: A Case Report - Formiga, Cibelle Kayenne Martins Roberto; Veloso, Aline Helena Nascimento; Fernandes, Kathlen Terezinha Montes Soares; Guimarães, Layra Alves; Avelar, Marla Moreira; Medeiros, Maja (Frontiers in Rehabilitation Sciences, 2022)
The COVID-19 pandemic raises concerns about risks for pregnant women and fetuses, considering factors such as vertical transmission and neonatal alterations caused by maternal infection. Despite this, neuropsychomotor and functional complications in infants delivered by mothers with COVID-19 are still little studied. Thus, we aimed to describe the health history of a high-risk preterm infant born to a mother hospitalized due to COVID-19 complications. This case report was based on medical records, outpatient follow-up, and maternal reports. The infant was born at thirty weeks and three days, weighing 1,300 g, measuring 40 cm, and with Apgar scores of 2, 5, 6, and 7. COVID-19 test was negative 1 h and 72 h after birth. Moreover, the infant had cardiorespiratory complications and hyperechogenicity of the periventricular white matter. The infant presented speech and language delays during follow-up, but neuromotor development occurred according to age. The health care and follow-up provided helped the development of resilience mechanisms by the infant and family to overcome adversities in the prenatal, perinatal, and neonatal periods.